2020
DOI: 10.3390/microorganisms8081114
|View full text |Cite
|
Sign up to set email alerts
|

16S and 23S rRNA Gene Mutation Independent Multidrug Resistance of Non-Tuberculous Mycobacteria Isolated from South Korean Soil

Abstract: Non-tuberculous mycobacteria (NTM) are ubiquitous microorganisms that have the potential to cause disease in both humans and animals. Recently, NTM infections have rapidly increased in South Korea, especially in urbanized areas. However, the distribution of species and the antibiotic resistance profile of NTM in environmental sources have not yet been investigated. Therefore, we analyzed the distribution of species and the antibiotic resistance profile of NTM in soil within urban areas of South Korea. A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Other countries with similar findings include China [39]- [41], Russia [42], America [43], [44], various countries in Europe [45] and Africa [11], [20], [46]- [48]. The high infectivity rate of MAC species could be attributed to their seemingly abundant nature and distribution in different environmental sources such as water and soil, consequently increasing its ease of spread and infection to humans [20], [49]. MAC has been highly associated with NTM-PD [50]; however, it remains unclear how its infectivity relates to NTM-PD [51].…”
Section: Discussionmentioning
confidence: 84%
“…Other countries with similar findings include China [39]- [41], Russia [42], America [43], [44], various countries in Europe [45] and Africa [11], [20], [46]- [48]. The high infectivity rate of MAC species could be attributed to their seemingly abundant nature and distribution in different environmental sources such as water and soil, consequently increasing its ease of spread and infection to humans [20], [49]. MAC has been highly associated with NTM-PD [50]; however, it remains unclear how its infectivity relates to NTM-PD [51].…”
Section: Discussionmentioning
confidence: 84%
“…In a similar manner, electron microscopy confirmed that the surface of Mmuc -R was more wrinkled and rough, while the surfaces of the strains Mmuc -ATCC and Mmuc -S were less wrinkled. Previous studies on the colony morphotypes of NTMs, including M. abscessus , have shown that rough morphotypes lacking GPLs induce a greater inflammatory response and more virulence than smooth morphotypes [ 5 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most NTMs that cause infections are challenging to treat and worsen the patient’s prognosis because they are resistant to the first-line drug for tuberculosis [ 4 ]. According to their growth rate, NTMs that grow on the media within or after 7 days are defined as rapidly growing mycobacteria (RGM) and slowly growing mycobacteria (SGM), respectively [ 5 ]. Of these, Mycobacterium mucogenicum ( Mmuc ) belongs to the RGM group [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, NTM infection mostly occurs by exposure to environmental sources because of the ubiquitous nature. Our previous study showed that MAC accounted for most of NTM isolated from soil that collected in animal shelter and parks 5 . Therefore, it is important to understand the pathogenicity of MAC in dogs not only for treatment and diagnosis but also to prevent potential zoonotic transmission between humans and dogs.…”
Section: Introductionmentioning
confidence: 99%